SISTEM PENYEDIAAN DAN DISTRIBUSI AIR BERSIH DI DESA TLOGOAGUNG KECAMATAN KEMBANGBAHU KABUPATEN LAMONGAN DENGAN EPANET 2.0 - Indrawati Wahyuni; Nur Azizah Affandy (Jurnal Teknika, 2018)
The availability of water is very important for human life, because water is a major human need. It is very important to plan a well-managed water supply system. Tlogoagung Village, Kembangbahu sub-district, Lamongan regency is one of the villages that have not yet a clean water distribution network, so it is necessary to plan clean water distribution network. The source of water used is the water source of the lake in the village. Clean water network system by making intake in lake then pumped to reservoir of distribution. Furthermore, it is distributed to the residential connection service area of the population with gravity system. A clean water network system is planned to meet the needs of clean water up to 2037. Clean water demand is calculated based on population projection by using linear analysis. From the calculation, the need of clean water in Tlogoagung village, Kembangbahu sub-district of Lamongan regency in 2036 with the population of 4431 populations reach 7,431 ltr / sec, for transmission pipes using pipes with 4 inch or 0.1016 m diameters. For distribution pipes using 3 inch diameter pipes 0.0762 m or 2 inch diameter or 0.0508, diameter 1 ½ or 0.0381 m, diameter 1 inch or 0.0254 m. To design a clean water distribution network using Epanet 2.0 software